2004
DOI: 10.1101/gr.2609605
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of a 0.5-Mb chicken region orthologous to the imprinted mammalianAscl2/Mash2–Igf2–H19region

Abstract: Previous studies revealed that Igf2 and Mpr/Igf2r are imprinted in eutherian mammals and marsupials but not in monotremes or birds. Igf2 lies in a large imprinted cluster in eutherians, and its imprinting is regulated by long-range mechanisms. As a step to understand how the imprinted cluster evolved, we have determined a 490-kb chicken sequence containing the orthologs of mammalian Ascl2/Mash2, Ins2 and Igf2. We found that most of the genes in this region are conserved between chickens and mammals, maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
43
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 69 publications
4
43
0
Order By: Relevance
“…DNMT1 (DNA methyltransferase 1) is a maintenance methyltransferase, which preferentially recognizes hemimethylated DNA and methylates the newly synthesized strand after DNA replication. Genetic studies in mice clearly showed that both classes of meth- zuki et al, 2005), but not in monotremes (egg-laying mammals such as platypuses and echidnas) (Killian et al, 2000) or birds (such as chicken) (O'Neill et al, 2000;Nolan et al, 2001;Yokomine et al, 2001Yokomine et al, , 2005. Thus, imprinting is restricted to placental mammals, which is consistent with the confl ict theory of imprinting evolution (Moore and Haig, 1991).…”
supporting
confidence: 68%
“…DNMT1 (DNA methyltransferase 1) is a maintenance methyltransferase, which preferentially recognizes hemimethylated DNA and methylates the newly synthesized strand after DNA replication. Genetic studies in mice clearly showed that both classes of meth- zuki et al, 2005), but not in monotremes (egg-laying mammals such as platypuses and echidnas) (Killian et al, 2000) or birds (such as chicken) (O'Neill et al, 2000;Nolan et al, 2001;Yokomine et al, 2001Yokomine et al, , 2005. Thus, imprinting is restricted to placental mammals, which is consistent with the confl ict theory of imprinting evolution (Moore and Haig, 1991).…”
supporting
confidence: 68%
“…Comparative mapping suggests these genes cluster on macrochromosomes in regions that preferentially undergo asynchronous DNA replication (Dunzinger et al 2005). Analysis of the chicken region orthologous to the imprinted mammalian ASCL2-H19 region (Yokomine et al 2005) revealed extensive conservation of gene organization, except H19, a critical noncoding imprinted gene. This gene and its regulatory elements were absent from the chicken genome.…”
Section: Comparative Genomicsmentioning
confidence: 99%
“…A surprising number of imprinted gene knockout models exhibit placental defects (19), suggesting gene dosage as another mechanism important in the evolution of the fetoplacental unit. Approximately 0.3% of autosomal genes are imprinted in eutherian mammals, while a subset of these genes are imprinted in marsupials with no evidence of imprinting in other vertebrates (1,31,32,37,39,51,54,56,58). Thus, the emergence of genomic imprinting coincides with the appearance of extraembryonic support, and, as the demands for this support have increased, the number of imprinted genes co-opted by the imprinting mechanism has increased (30), also suggesting the involvement of these unique genes in placental development.…”
mentioning
confidence: 97%